Strengthening Islamic Religious Education Values in Developing Independent Character - Ikhwanul Abrori; Tobroni; Romelah; Ikhwan, Afiful (LETIGES, 2024)
This study explores the strengthening of Islamic Religious Education values at the Nyai Ahmad Dahlan Ponorogo Child Welfare Institution (LKSA NAD) in developing foster children's independence. This study uses a qualitative approach with a case study. Data were collected through interviews, observations, and documents. Validity was tested by triangulation, and data analysis was carried out using the Miles interactive model, including collection, condensation, presentation, and conclusion. Strengthening the values of Islamic Education (PAI) at LKSA NAD plays a vital role in developing the character of independence of foster children. Strengthening the values of PAI at LKSA NAD is carried out through material, habituation, and lectures. Strengthening the material includes memorisation of the qur'an, interpretation, the qur'an and hadith, aqidah akhlaq, fiqh, and imla, qira'ah (recitation), arabic language learning, muhadarah (speech), al-Islam and Muhammadiyah, tartil reading the qur'an. Habituation is carried out through activities at the Ramadhan short-term boarding school, obligatory and sunnah worship, while lectures are given in religious study (kajian). This program has successfully increased foster children's independence, especially in making independent decisions, understanding moral values, and preparing themselves professionally with Islamic ethics. Foster children realise the benefits of this program in facing independent life in the future, although it was initially challenging. Materials such as memorising the qur'an, aqidah akhlaq, fiqh, and muhadarah are essential in strengthening PAI values. This study shows that strengthening Islamic Education values significantly contributes to increasing foster children's independence through Islamic ethics and responsible decision-making skills.